2008
DOI: 10.1007/s00520-008-0555-5
|View full text |Cite
|
Sign up to set email alerts
|

Resounding attachment: cancer inpatients’ song lyrics for their children in music therapy

Abstract: Parents' song lyric messages may support their children during the parents' illnesses and through the children's developmental transitions and possible bereavement. Some parents use song writing for catharsis and to encourage their children's continuing attachment with them after death. Through promoting parent-child connectedness and emotional expression, therapeutic song writing can be a valuable oncologic supportive care modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…O'Callaghan and colleagues [33] analyzed the lyrics of songs written by parents with metastatic cancer to their children. They found that parents used these songs as a way to facilitate their child's sense of connectedness to the hospitalized parent and as a way to ensure ongoing attachment to them after death [33]. Drawing on ethnographic fieldwork at a support group for women with metastatic cancer, Bell and Ristovski-Slijepcevic [26] explored the relationship between mothering and living with advanced cancer.…”
Section: Severe Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Callaghan and colleagues [33] analyzed the lyrics of songs written by parents with metastatic cancer to their children. They found that parents used these songs as a way to facilitate their child's sense of connectedness to the hospitalized parent and as a way to ensure ongoing attachment to them after death [33]. Drawing on ethnographic fieldwork at a support group for women with metastatic cancer, Bell and Ristovski-Slijepcevic [26] explored the relationship between mothering and living with advanced cancer.…”
Section: Severe Reactionsmentioning
confidence: 99%
“…Creswell [47] recommended researchers employ at least two of these strategies in any given study to achieve adequate trustworthiness of their findings. Seven of the included studies used two or more of these strategies to ensure trustworthiness including use of field notes, clear description of analysis, direct quotations from participants, rich thick descriptions, extended fieldwork, peer review, reflexivity, investigator triangulation, data triangulation, inter-coder reliability, and audit trails [25][26][27][28][29][30][31][32][33].…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…As a result of such combined treatments the patients and their family members can experience a kind of social support, and they can get a greater opportunity for expressing their needs on both verbal and nonverbal levels. In another experiment (O'Callaghan, O'Brien, Magill, & Ballinger, 2009) mothers and fathers having haematological or metastatic diseases songs for their children. Parents' song lyric messages may support their children during the parents' illnesses and through the children's developmental transitions and possible bereavement.…”
Section: Application Of Music With Children Having Cancermentioning
confidence: 99%
“…Thoughts, feelings, memories, and life situations were discussed as superficially or in-depth as comfortable for the participants, with the music therapist asking open-ended questions when needed to further guide the process and ensure that all participants had a chance to talk. O'Callaghan, C., O'Brien, E., Magill, L. & Ballinger, E. (2009). Resounding attachment:…”
Section: Music Listening and Discussionmentioning
confidence: 99%
“…Six control group participants, due to personal time and travel constraints, did not complete a music therapy session after their control group period was over. were developed by the principal investigator based on research and clinical work (Antoni, 2003;Gfeller, 2008;Miller & O'Callaghan, 2010;O'Callaghan, O'Brien, Magill, & Ballinger, 2009;Pelletier, 2004;Reuer, 2006;Standley, 1986;Thaut, 2005), in conjunction with verbal and written feedback from previous participants in music therapy sessions. In addition, another board-certified music therapist experienced in music therapy and cancer care reviewed the final selection of topics and interventions.…”
Section: Music Therapy Support Group Numerical Rating Scales (Mtsg-nrs)mentioning
confidence: 99%